“Desire Is Like a Dreadful Monster”: Analysis of Extended Metaphors in L2 Argumentative Essays by Chinese Learners of English - Lu, Qiuyun (Frontiers in Psychology, 2021)
This article explores the use, function, and understanding of extended metaphors in L2 argumentative essays by Chinese learners of English. The analysis starts with the identification of linguistic metaphors and extended metaphors in 72 argumentative texts produced by 37 intermediate Chinese English majors. The function of extended metaphors is then analyzed by adopting the bottom-up approach of establishing systematic metaphors from those identified extended metaphors, to draw learners’ communicative intentions in producing extended metaphors. To understand learners’ thinking processes behind using extended metaphors while writing, four of nine writers were interviewed about the process of writing extended metaphors in their texts in the stimulated recall interviews. It is found that extended metaphors, expressed through similes or direct metaphors at strategic stages in L2 argumentative essays, are often the result of learners’ conscious manipulation of L1 in producing L2 for various communicative purposes, such as the desire for vividness, coherence, comprehensibility, when there is a knowledge gap between L1 and L2, and for evaluative and persuasive power. These communicative functions are consistent with the ideational, interpersonal, and textual functions of language, which also coincide and interact with the rhetorical goals of moves and stages in L2 argumentative essays. Metaphoric thinking, L1 influence, and struggling to express meaning and persuade, cited in learners’ thought reports, are major factors triggering extended metaphors. The findings of this article can contribute to the knowledge of learners’ metaphoric competence in L2, which can, in turn, enrich teachers’ metaphor knowledge and draw teachers’ attention to learners’ creative ways of using metaphors and then raise metaphor awareness in L2 writing, teaching, and learning.